Basis of mathematics and methods of teaching - Arkadijus Kiseliovas; Danutė Genienė (Lietuvos Matematikos Rinkinys)
In the article is analyzed problems of alteration and integration of mathematical basis and its teaching methods that is lecturing at Pedagogical faculty.